Wetland ecosystem modelling and valuation in Kalu Oya Basin, Sri Lanka - International Water Management Institute (International Water Management Institute, 2024)
IWMI, in partnership with the Sri Lanka Land Development Corporation, Kings College London and AmbioTEK, is conducting a project on wetland ecosystem modelling and economic valuation in the Kalu Oya and Mudun Ela Basins in Sri Lanka.